The Influence of Diabetic Exercise on Decreasing Blood Sugar Levels in Diabetes Mellitus Patients at Bah Kapul Health Center, Pematangsiantar - Sri Wahyuni Tarigan (Science Midwifery, 2022)
Diabetic gymnastics is physical exercise that is designed according to age and physical status and is part of the treatment of diabetes mellitus. The diabetes exercise used is low impact aerobic exercise which can increase the use of glucose by active muscles so that it can directly lower blood glucose. This study aims to determine the effect of diabetes exercise on reducing blood sugar levels in diabetic patients at the Bahkapul Health Center , Pematangsiantar . This research was conducted in June - August 2017, the research design was comparative. The number of samples in this study were 21 respondents who were obtained by taking the total sample method . Data were obtained through questionnaires, interviews and direct sampling of the respondent's capillary blood and then measuring their blood sugar levels using a glucose meter. Data analysis was carried out in stages including univariate analysis and bivariate analysis using paired t-tests . The results of this study indicate that before doing gymnastics in the first week the average respondent's blood sugar level was 272.4 mg /dl and after doing gymnastics in the fourth week the average respondent's blood sugar level was 257.04 mg/dl. blood sugar of 15.36 mg/dl. The results of the analysis using the paired t-test significantly decreased blood sugar levels in respondents with a p value <0.05 , namely 0.041. This means that there is an effect of diabetes exercise on reducing blood sugar levels in diabetic patients. It is hoped that health services can become a motivator and provide intensive counseling for people with diabetes mellitus to do routine diabetes exercise to lower blood sugar levels and prevent complications of diabetes mellitus.